IMPLEMENTASI PROGRAM WAJIB BELAJAR SEMBILAN (9) TAHUN PADA LEMBAGA PENDIDIKAN MUHAMMADIYAH DI MANDAILING NATAL - Rizaluddin Rizaluddin (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: Education is one of the most important things and cannot be separated from life. Education can promote culture and uphold the nation in the eyes of the international community. The thinking of advanced society will form the Human Resources of good quality in terms of spiritual, intelligence and high skills. Therefore, it was necessary to improve the quality of education. So that our nation does not depend on the status of a developing nation but can bear the predicate of a developed nation and no less competitive with the European nation. An overview of the achievement of the nine years Compulsory Education through 2015-2017 shows that the Participation Grade rate at the junior high school / equivalent level has reached at least 95%. In 2009 the National Rough Participation Rate has reached 98.11%, so the 9-year compulsory education program has been completed in accordance with the time targeted by the Indonesian government and even that target can be achieved 7 years earlier than the declared international commitment in Dakar on Education for All (EFA) in 2000 which requires all countries in the world to complete 9 years compulsory education by 2015. Based on these considerations, the study sites of two MTs Muhammadiyah institutions in Kotanopan (Mandailing Natal Regency) were selected. The main problem in this researchwas